The Incidence of Skin Allergy Testing Antivenom and its Related Factors in Behbahan - Rafi, Alireza; Mousavi, Keyvan; Etebari, Atefeh; Davoodi, Narjes; Darabiyan, Pouriya; Sabaghan, Mohamad (International Research in Medical and Health Sciences, 2020)
Introduction: Immunotherapy is the only treatment of scorpion sting antidote is immune from severe scorpion sting is an effective treatment for horses. Anaphylaxis is a life-threatening adverse reaction to antidote and is a major concern in the use of antidote is usually the symptoms of wheezing, itching, hives secretion, bronchospasm, hypotension, bradycardia, myocardial infarction, and cyanosis. Since research has been done in this regard, the study investigated the incidence of skin allergy testing antivenom and its related factors in Behbahan.Materials and Methods: This study was a cross-sectional study was approved by the Review questionnaire of the Ministry of Health on Scorpion patients in the Disease Control and Prevention Center of Shahidzadeh Hospital in Behbahan was conducted from 2007 to 2017. The required data through a data entry form includes information such as age, sex, sensitivity Whether or not the antidote, the time of the bite history, admission, location of the bite, location, and type of Scorpio, were collected from patients' records. Data using statistical software spss version 18 and descriptive statistics were analyzed and binomial test.Results: In this study over 10 years, 184 cases were observed with antivenom allergy. Of these, 83 (45.1%) were male and the rest female. Also, 64.1 percent of rural residents and settlers, maximum bite in the upper extremities (with 21.7 percent). Most allergies in the early hours of the morning sting 35.3 percent (6-0 am), respectively. 29-20year age group had the highest sensitivity to antibiotics by 29 percent. In the spring with 57.01%and winter by 06.5 percent were the most and least sensitive to the antivenom. In the meantime, the sting to admit was 435.92 minutes. People who are not sensitive in the meantime was 370.07 minutes, there was a significant difference between the two groups (p= 0.016).Conclusions: Due to the high prevalence of antivenom allergy in the spring, warm months and those living in rural areas seem these factors play an important role in increasing susceptibility to antidote. And to reduce the number of sensitivity and its complications due to these cases is necessary.